Abiotic soil properties affecting interpretation of IRIS sensors in tidal and freshwater soils. Issue 6 (31st August 2021) - Romero, Jasper; Hino, Katelyn; Loffredo, Joseph; Stolt, Mark; Moseman‐Valtierra, Serena; Amador, Jose; Pellock, Brett
Abstract: Indicator of Reduction in Soils (IRIS) films are visual sensors used to document weakly or moderately reducing conditions in soils based on the reduction and removal of brown manganese (Mn) oxide or orange iron (Fe) oxide paints, respectively, from underlying white polyvinyl chloride (PVC) films. Paint removal is largely assumed to result from anaerobic microbial reduction using metal oxides on the PVC films as electron acceptors. If true, IRIS films could indicate conditions favorable to other biogeochemical processes that occur at similar redox potentials to those facilitating paint removal. Our objective here was to assess the effects of selected abiotic soil properties on IRIS film paint removal to determine whether removal can accurately be attributed to biotic processes alone. Through field deployments and laboratory incubation experiments using IRIS films, we investigated relative sulfide concentration and dissolved organic matter as two abiotic factors potentially capable of removing paint from Mn IRIS films. Our results showed that abundance of reactive soluble sulfides cause rapid and extensive abiotic paint removal from Mn films, whereas ambient concentrations of dissolved organic matter in freshwater wetland porewater does not drive abiotic removal. Furthermore, we found that the visible formation of black iron monosulfides on Fe films can be used to detect sulfide concentrations that will remove paint from Mn films. This study suggests that whereas some abiotic soil properties (e.g., sulfide concentration) can cause paint removal, IRIS films may be a viable tool to approximate biotic process rates where abiotic paint removal can be ruled out. Core Ideas: We tested the assumption that IRIS film paint removal reflects largely biotic reduction. In controlled experiments, we assessed the effects of two abiotic soil properties on IRIS films. Reactive soluble sulfides, but not dissolved organic matter, removed IRIS paint abiotically. Iron IRIS films can detect sulfide concentrations that bias signals on Mn films. Biotic IRIS film signals may indicate conditions favoring ecologically valuable biogeochemistry.